Pediatric granular cell tumor of vulva: A rare benign tumor - Shannon M. Howard; Bhairav Shah; Kristl V. Tomlin (Elsevier, 2021)
We present a rare case of a school-aged girl with granular cell tumor of the vulva. The patient presented with a right labial swelling of unknown duration. Initial diagnostic workup with ultrasound suggested a gonadal structure in the right labia, which was read as ovarian herniation through the Canal of Nuck into the right labia majora. Given concerns for a concurrent Mullerian dysgenesis syndrome predisposing the patient to ovarian herniation, the patient was scheduled for a diagnostic laparoscopy and hernia repair with possible excision of vulvar mass. Laparoscopy revealed normal reproductive anatomy with two visualized normal appearing pelvic ovaries. Subsequent excision of the mass was determined to be granular cell tumor by pathology. There are fewer than 20 reported cases of pediatric vulvar granular cell tumors in the literature and no reports of granular cell tumors presenting as ovarian structure on imaging. This case highlights the importance of including this rare tumor in the differential diagnosis for vulvar mass which may be misread as ovary on ultrasound.